Legal Education in Pakistan: an Overview of Stakeholders’ Perception - Shah, Sardar Ali; Dhanapal, Saroja; Syed, Kazim (Journal of Legal Studies, 2024)
Legal education plays a vital role in the country's justice system. The graduates with good quality of law education have a great impact on the quality of the judiciary, Bar, and Bench. There is a general perception amongst the stakeholders comprising of that the present legal education in Pakistan does not satisfactorily match the needs of the country. Thus, it needs to be reviewed and reformed. In line with this, the objective of the current qualitative study is to analyze the opinions of stakeholders. The article ends with recommendations for improvement in legal education as advocated by the stakeholders.